2022
DOI: 10.3390/pathogens11090962
|View full text |Cite
|
Sign up to set email alerts
|

First Isolation and Characteristics of Bovine Parainfluenza Virus Type 3 from Yaks

Abstract: The yaks belong to the genus Bos within the family Bovidae that live in the Tibet Plateau and is an indispensable economic resource for the local herders. Respiratory tract infections are common diseases in yaks caused by various pathogens; however, there have been no reports of bovine parainfluenza virus type 3 (BPIV3) infection. This study was conducted to investigate the pathogens and analyze their characteristics from the four yak lung samples with severe respiratory tract infection symptoms in the yak far… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 45 publications
1
6
1
2
Order By: Relevance
“…The results showed that all guinea pigs developed significant respiratory symptoms and pathological lung changes after being intranasally inoculated with the isolates. Our findings differed from previous investigations [ 18 , 33 , 34 , 35 , 36 ], which may be related to the animal species and the virulence of the strains. Among three infection groups, guinea pigs inoculated with Hubei-03 had the most obvious clinical symptoms, the most obvious pathological changes, and the highest viral load in the lungs, which indicated that the pathogenicity of the Hubei-03 strain had the highest virulence among all the isolated viruses.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The results showed that all guinea pigs developed significant respiratory symptoms and pathological lung changes after being intranasally inoculated with the isolates. Our findings differed from previous investigations [ 18 , 33 , 34 , 35 , 36 ], which may be related to the animal species and the virulence of the strains. Among three infection groups, guinea pigs inoculated with Hubei-03 had the most obvious clinical symptoms, the most obvious pathological changes, and the highest viral load in the lungs, which indicated that the pathogenicity of the Hubei-03 strain had the highest virulence among all the isolated viruses.…”
Section: Discussioncontrasting
confidence: 99%
“…Here, we reported a 13.16% (95% CI: 4.41–28.09) (5/38) BPIV-3 herd-level and 4.64% (95% CI: 2.56–7.66) (14/302) individual-level proportion in cattle, indicating that BPIV-3 commonly exists in cattle farms with BRDC outbreaks in China, which is consistent with a previous limited study [ 17 ]. The predominant genotype of BPIV-3 in China is C [ 5 , 14 , 18 ], which also aligned with our results.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…To confirm the SC strain isolated in MDBK cells, RNA from virus-infected supernatant was extracted using TRIzol reagent (Invitrogen, Waltham, MA, USA) and then tested using the specific RT-PCR method. Two pairs of primers, BPIV-3-F1 (GAATGACTCATGATAGAGGTAT) and BPIV-3-R1 (AGGACAACCAGTTGTATTACAT) and BPIV-3-F2 (GCTCTTCTCTTTTTGTCCCATTCTT) and BPIV-3-R2 (AACCCCTTCCTCA ATCCTGATATAC), were used here to confirm the presence of BPIV-3 SC with the corresponding PCR amplicons of 647 bp and 422 bp, respectively [21,25].…”
Section: Virus Isolationmentioning
confidence: 99%
“…The HEK293 and MDBK cell lines are preserved in our laboratory. BPIV3 genotype C (SMU-SC20) strain (GenBank: OM621819.1) [29] and BPIV3 genotype A (B15) strain (GenBank: PP025529.1) were isolated from yaks and water buffaloes suffering from BRDC, respectively. This viruses titer were 1×10 6.5 TCID 50 /mL and 1×10 6.45 TCID 50 /mL, respectively [29].…”
Section: Cells Lines and Virusesmentioning
confidence: 99%